2011
DOI: 10.1161/atvbaha.111.232223
|View full text |Cite
|
Sign up to set email alerts
|

Premature Senescence in Cells From Patients With Autosomal Recessive Hypercholesterolemia (ARH)

Abstract: Objective-The defective gene causing autosomal recessive hypercholesterolemia (ARH) encodes ARH, a clathrinassociated adaptor protein required for low-density-lipoprotein receptor endocytosis in most cells but not in skin fibroblasts. The aim here was to elucidate why ARH fibroblasts grow slowly and undergo premature senescence. Methods and Results-Knockdown of ARH by RNA interference in IMR90 cells produces the same phenotype, indicated by increased p16 expression, ␥-H2AX-positive foci, and enlarged flattened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Thus, the putative CDK1 target site pS14 is up-regulated in mitosis and its deletion or mutation leads to defective mitotic spindle formation suggesting an important role for Ldlrap1 in the mitotic cell cycle [36]. We find pS14 robustly down-regulated again supporting the idea of cAMP-induced cell cycle arrest.…”
Section: Resultssupporting
confidence: 67%
“…Thus, the putative CDK1 target site pS14 is up-regulated in mitosis and its deletion or mutation leads to defective mitotic spindle formation suggesting an important role for Ldlrap1 in the mitotic cell cycle [36]. We find pS14 robustly down-regulated again supporting the idea of cAMP-induced cell cycle arrest.…”
Section: Resultssupporting
confidence: 67%
“…Figures 8A and 8B show that infection of human VSMC with Ad133a results in significantly less proliferation of those cells, compared with scrambled control virus (98.6 ×10 3 +/−9.5 × 10 3 vs 50.6 × 10 3 +/−3.2 × 10 3 , P<0.01). Limited literature suggests LDLRAP1 may have cell-specific functions unrelated to LDLR internalization [40]. To determine if LDLRAP1 played a role in VSMC proliferation, human VSMC were transfected with LDLRAP1-specific siRNA, and VSMC proliferation quantitated.…”
Section: 0 Resultsmentioning
confidence: 99%
“…This hypercholesterolemia is assumed to be a result of impaired LDL internalization by hepatocytes, and disruption of LDLRAP1 results in 80% reduction in LDL internalization in cultured hepatocytes [31,32,35]. Importantly, LDLRAP1 function has been posited to be tissue specific [40], as hepatocytes and lymphoblasts from ARH patients display impaired LDL internalization, but internalization is normal in fibroblasts from the same patients. The transformation of VSMC into foam cells is a key step in atherogenesis [2].…”
Section: 0 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of LDLRAP1 in the kidneys has been described as playing a key role in potassium homeostasis, at least in mice 21) . Another article indicated that LDLRAP1 proteins are involved in cell cycle progression, possibly via effects on nuclear membrane formation through their interactions with mitotic proteins 22) . However, there is no evidence of primary potassium retention, hyperkalemia or premature aging in human ARH subjects.…”
Section: Role Of the Ldl Receptor And Its Related Proteinsmentioning
confidence: 99%